Perlindungan Hak Atas Kebebasan Beragama dan Beribadah dalam Negara Hukum Indonesia - Fatmawati, Fatmawati (Jurnal Konstitusi, 2011)
The first principle of Pancasila recognized God Almighty, which means the duty of every man  in  Indonesia  to  respect  the  religion  and beliefs of others, because it is everyone’s right to choose, embrace, and practice the teachings of their religion freely without interference and without  disturbing  others.  It  means  not only ban unethical proselytism, but also ban desecration and abuse of religion in the Republic of Indonesia to protect security and public order to avoid unrest in society. It is set in the first principle of Pancasila and    was animated in articles of the Constitution (Article 28E Paragraph (1) and Article 29) regulating the right of religion and worship, which is   then further regulated in some legislations, among other Law Number 39 Year 1999 on Human Rights and Law No. 1/PNPS/1965 on the Prevention of Abuse and / or Blasphemy. Restrictions on the freedom to perform and determine one’s religion or belief under article 18 paragraph (3) of the ICCPR can only be limited by provisions of law,  and it is  needed to protect public safety, order, health, or morals of the fundamental rights and freedoms of others; and the regulation in Article 11 of Law No. 1/ PNPS/1965 has met the criteria for the application of restrictions on the freedom to perform and determine one’s religion or beliefs, in the sense that the restriction is the conduct of the teaching and not in his belief, by law, and to protect security and public order to avoid unrest in society.